Minimum Wages and the Health of Hispanic Women - Susan L. Averett; Julie K. Smith; Yang Wang (Institute of Labor Economics (IZA), 2017)
States are increasingly resorting to raising the minimum wage to boost the earnings of those at the bottom of the income distribution. In this paper, we examine the effects of minimum wage increases on the health of low-educated Hispanic women, who constitute a growing part of the U.S. labor force, are disproportionately represented in minimum wage jobs and typically have less access to health care. Using a difference-in-differences identification strategy and data drawn from the Behavior Risk Factor Surveillance Survey and the Current Population Survey from the years 1994–2015, we find little evidence that low-educated Hispanic women likely affected by minimum wage increases experience any changes in health status, access to care, or use of preventive care.
Keywords: J15; I12; I13; I14; 330; minimum wage; Hispanic women; health outcomes; health insurance; preventive care